The effect of gembili flour (Dioscorea esculenta L.) substitution on dietary fiber contents, sensory, and chemical characteristics of cookies - Eko Yuliastuti Endah Sulistyawati; Rina Rismaya; Adhi Susilo; Dini Nur Hakiki; Alutsyah Luthfian (Hasanuddin University Food Science and Technology Study Program, 2024)
Cookies are preferred by many people of all ages but are poor in dietary fiber. Gembili (Dioscorea esculenta L.) is a high-fiber local food ingredient, which is quite abundant in Indonesia but has not been utilized optimally. The purpose of this study was to determine the effect of gembili flour substitution on dietary fiber contents and chemical and sensory characteristics of cookies. This study used a one factor completely randomized design with three treatment levels of gembili flour substitution (0%, 50%, and 100%), which were repeated three times. Gembili flour substitution significantly increased the ash content and dietary fiber but significantly decreased the sensory quality and protein content of cookies. Based on the sensory evaluation, cookies with 50% substitution of gembili flour were the selected product because these did not differ significantly from the control cookies (0% gembili flour) for all sensory attributes tested, except for aroma. Although the hedonic ratings of gembili flour cookies were still lower than those of the control cookies, they contained a higher content of dietary fiber. Therefore, gembili flour, which is high in dietary fiber content, can be used as a functional ingredient in cookies and in other bakery products. These findings are expected to provide new insights for research and bakery industries in developing high fiber cookies from local food sources.